Comparison of the Effectiveness of Chemo-mechanical and Traditional Caries Removal Methods in Primary Teeth Using Micro-Computed Tomography - Firdevs Tulga Öz; Melike Turgut Coşgun; Kaan Orhan; Mert Ocak (Ankara University, 2021)
Objective: The purpose of this study was to evaluate dentin mineral density before and after caries removal with the traditional caries removal technique and chemo mechanical method, with or without the use of caries detection dye. Our null hypothesis was that the chemo mechanical method with minimally invasive treatment would achieve an effect similar to that of conservative pediatric dentistry treatment. Forty-eight extracted human primary molar were used in this study. Materials and Methods: The two main study groups underwent treatment with the chemo mechanical and traditional methods. The teeth were then treated with chemo mechanical and traditional caries removal approach. Teeth were scanned with the same voxel sizes using micro-CT images to figure out the difference dentin mineral density and to calculate the removed (excavated) dentinal volume after chemo mechanical or traditional method application. Results: The results showed increase of cavity volume in the chemo mechanical and traditional method groups. No significant difference was found for cavity volume and dentinal carious volume in both groups (p˃0,05). The mineral density values of demineralized dentin were between 0.52-0.66 g/cm3 before caries removal, and 1.39-1.59 g/cm3 after removing caries. These values were found to be within the range of healthy dentin mineral density values again without any significant difference between groups (p˃0,05). Conclusions: In conclusion, chemo mechanical can be used effectively for removing the caries in the primary molar teeth similar to conservative treatments.